2020
DOI: 10.3389/fvets.2020.00536
|View full text |Cite
|
Sign up to set email alerts
|

Transcallosal Removal of a Choroid Plexus Tumor From the Lateral Ventricle in a Dog. Case Report

Abstract: A 6-years-old female Staffordshire terrier was referred for periodic generalized seizures and asymmetric visual deficits. Magnetic resonance imaging revealed a 23.2 × 19.3 × 23.0 mm soft tissue mass within the right lateral ventricle and consequential dilatation of the lateral ventricles. Surgically, an interhemispheric approach was performed next to the marginal gyrus after a right parieto-parasagittal craniotomy, and a large choroid plexus tumor was transcallosally removed. After 3 days, the dog was discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…15 The survival time of another dog following surgical resection of a choroid plexus papilloma from the lateral ventricle through a transcallosal approach was at least 9 months. 16 Treggiari et al reported a median survival time of 3 years in dogs with infratentorial tumors. 17 Two of the dogs included in that study were diagnosed with a choroid plexus tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The survival time of another dog following surgical resection of a choroid plexus papilloma from the lateral ventricle through a transcallosal approach was at least 9 months. 16 Treggiari et al reported a median survival time of 3 years in dogs with infratentorial tumors. 17 Two of the dogs included in that study were diagnosed with a choroid plexus tumor.…”
Section: Discussionmentioning
confidence: 99%
“…However neurological deficits persisted throughout the dog's life 15 . The survival time of another dog following surgical resection of a choroid plexus papilloma from the lateral ventricle through a transcallosal approach was at least 9 months 16 . Treggiari et al reported a median survival time of 3 years in dogs with infratentorial tumors 17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of histological diagnosis for the tumor in this case and therefore the potential response to RT is a limitation of the case report. For tumors in the III ventricle, surgical resection has been successfully attempted in veterinary medicine ( 34 , 35 ). However, due to the very challenging location, it carries a high rate of complications and post-operative mortality, hence was not attempted in this case ( 4 , 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, the majority of studies concerning surgical treatment of brain tumors exist for meningiomas, which are normally much easier to access than intra-axial or intraventricular mass lesions [ 32 ]. There are only two reports about surgical treated intracranial CPTs in dogs which were located in the lateral and fourth ventricle and in which a tumor resection was performed via interhemispheric-transcallosal and a telovelar approach, respectively [ 34 , 35 ]. In both cases, the tumor was confirmed as CPP and both dogs demonstrated a favorable outcome with surgery.…”
Section: Discussionmentioning
confidence: 99%